The top three burning questions in total hip arthroplasty - Manouras, Lefteris; Bastian, Johannes Dominik; Beckmann, Nicholas A.; Tosounidis, Theodoros H. (Medicina, 2023)
Total hip arthroplasty (THA) for end-stage osteoarthritis is one of the most effective surgical treatments in medicine. Impressive outcomes have been well documented in the literature with patients gaining ambulation and recovery of hip joint function. Nevertheless, there are still debatable issues and controversies that the orthopedic community has not been able to provide a definitive answer for. This review is focused on the current three most debatable issues surrounding the THA procedure: (1) new cutting-edge technology, (2) spinopelvic mobility, and (3) fast-track protocols. The scope of the herein narrative review is to analyze the debatable issues surrounding the three aforementioned topics and conclude the best contemporary clinical approaches regarding each issue.
Gesehen am 17.10.2023